New Information in Naturalistic Data Is Also Signalled by Pitch Movement: An Analysis from Monolingual English/Spanish and Bilingual Spanish Speakers - Gries, Stefan Th.; Miglio, Viola G. (Complutense Journal of English Studies, 2014)
In communication, speakers and listeners need ways to highlight certain information and relegate other information to the background. They also need to keep track of what information they (think they) have already communicated to the listener, and of the listeners' (supposed) knowledge of topics and referents. This knowledge and its layout in the utterance is commonly referred to as information structure, i.e., the degree to which propositions and referents are given or new. All languages have 'chosen' different ways to encode such information structure, for instance by modifying the pitch or intensity of the vocal signal or the order of words in a sentence. In this study, we assess whether the use of pitch to signal new information holds in typologically different languages such as English and Spanish by analyzing three population group monolingual California English speakers, bilingual speakers of English and Spanish from California (Chicano Spanish), and monolingual Mexican Spanish speakers from Mexico City. Our study goes beyond previous work in several respects. First, most current work is based on sentences just read or elicited in response to highly standardized and often somewhat artificial stimuli whose generalizability to more naturalistic settings may be questionable. We opted instead to use semidirected interviews whose more naturalistic setting provides data with a higher degree of authenticity. Second, in order to deal with the resulting higher degree of noise in the data as well as the inherent multifactoriality of the data, we are using state-of-the-art statistical methods to explore our data, namely generalized linear mixed-effects modeling, to accommodate speaker- and lexically-specific variability. Despite the noisy data, we find that contour tones including H+L or L+H sequences signal new information, and that items encoding new information also exhibit proportionally longer stressed vowels, than those encoding given information. We also find cross-dialectal variation between monolingual Mexican Spanish speakers on the one hand and monolingual English speakers and Chicanos on the other: Mexican Spanish speakers modify pitch contours less than monolingual English speakers, whereas the English patterns affect even the Spanish pronunciation of early bilinguals. Our findings, therefore, corroborate Gussenhoven's theory (2002) that some aspects of intonation are shared cross-linguistically (longer vowel length & higher pitch for new info), whereas others are encoded language-specifically and vary even across dialects (pitch excursion & the packaging of information structure).